Perancangan Prototype Sistem Informasi Pendaftaran Hak Kekayaan Intelektual (HKI) pada Dinas Perindustrian Provinsi Sumatera Selatan - Rindi Rama Saputra; Deni Erlansyah (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aims to design a prototype of a web-based Intellectual Property Rights (IPR) registration information system at the South Sumatra Provincial Industry Office as an effort to support the improvement of public service quality. The main problem faced by partners is the manual registration and management process for IPR data, which has the potential to cause service delays, data recording errors, and difficulties in monitoring the status of IPR applications. This condition requires an information technology-based solution that can improve the efficiency, effectiveness, and transparency of services. The method used in this community service activity is the prototype method, which includes the stages of problem identification, user needs analysis, system design, and initial evaluation of the resulting prototype. The designed information system prototype includes features for online IPR registration, applicant and document data management, and application status monitoring. The results of the activity indicate that the IPR registration information system prototype is able to provide an overview of digital solutions that are in accordance with partner needs and have the potential to improve service efficiency and ease of data management. This activity is expected to become the basis for the development of a more comprehensive and sustainable IPR information system within the South Sumatra Provincial Industry Office.